A probable case of sporadic variant Creutzfeldt-Jacob disease with long survival in Peru - Bancalari-Benavides, Ernesto (2021)
Creutzfeldt-Jakob disease (CJD) is the commonest human prion disease with a reported annual incidence rate of one per million worldwide. CJD has a bad prognosis, and the mean length of survival is 4-6 months. Only 11 cases have been reported in the literature from Perú. Thus, we report a case of a 66-year-old male patient with the diagnosis of probable sporadic CJD in whom the survival duration was of 25 months. We identify that the time from disease onset to myoclonus and to reach the akinetic mutism state, the absence of early imaging findings, the delayed cortical and basal ganglia involvement and the supportive therapies implemented were factors that could contribute for the long survival in this patient.